2008
DOI: 10.1302/0301-620x.90b8.20595
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative injections of epoetin-α versus post-operative retransfusion of autologous shed blood in total hip and knee replacement

Abstract: This prospective randomised clinical trial evaluated the effect of alternatives for allogeneic blood transfusions after total hip replacement and total knee replacement in patients with pre-operative haemoglobin levels between 10.0 g/dl and 13.0 g/dl. A total of 100 patients were randomly allocated to the Eprex (pre-operative injections of epoetin) or Bellovac groups (post-operative retransfusion of shed blood). Allogeneic blood transfusions were administered according to hospital policy. In the Eprex group, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…RA patients are more prone to receive blood product transfusions postoperatively. Appropriate blood loss and transfusion management should be deliberated in due time in patients suffering from RA, including shed blood retransfusion, preparation of autologous blood as well as preoperative injection of epoetin [28, 42] . The finding of increased requirement for health care resources may in part pertain to the more thorough preparation for surgery that RA patients receive.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients are more prone to receive blood product transfusions postoperatively. Appropriate blood loss and transfusion management should be deliberated in due time in patients suffering from RA, including shed blood retransfusion, preparation of autologous blood as well as preoperative injection of epoetin [28, 42] . The finding of increased requirement for health care resources may in part pertain to the more thorough preparation for surgery that RA patients receive.…”
Section: Discussionmentioning
confidence: 99%
“…The use of recombinant human erythropoietin or autologous blood transfusion pre-operatively have been suggested as ways to manage preoperative anaemia [26,27]. A review of the evidence based outcomes of the different supplementations in hip and knee surgery suggested that iron therapy, both oral and intravenous have been shown to reduce the need for allogeneic blood transfusion and significantly reduced the post-operative infection rate [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review comparing the evidence of administering erythropoietin with iron supplements to an active control group of either iron supplementation or cell salvage [26,30], showed that the clinical outcomes of post-operative infections, length of stay and 30 day mortality were generally not significant when compared to the active control group in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in blood loss management has been thoroughly studied, showing a 60% reduction of ABTs in patients who received EPO compared to control group[28-30]. Three or four weekly subcutaneous injections (600 IU/kg) seems to be the most frequently used protocol with the best results[31-35]. Weber et al[36] reports a mean rise in pre-operative Hb of 1.9 g/dL in patients that received EPO.…”
Section: Pre-operativementioning
confidence: 99%